2018
DOI: 10.1016/j.jpainsymman.2017.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Policy Studies Group: Two Decades of Working to Address Regulatory Barriers to Improve Opioid Availability and Accessibility Around the World

Abstract: For two decades, the Pain & Policy Studies Group (PPSG), a global research program at the University of Wisconsin Carbone Cancer Center, has worked passionately to fulfill its mission of improving pain relief by achieving balanced access to opioids worldwide. PPSG's early work highlighted the conceptual framework of balance leading to the development of the seminal guidelines and criteria for evaluating opioid policy. It has collaborated at the global level with United Nations agencies to promote access to opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…National laws and regulations governing opioids typically focus on prevention of diversion and illegal use of opioids and make production importation, and prescription of morphine and other opioids difficult or impossible (25). For this and other reasons, including supply chain logistics and a dearth of manufacturers, stock outs of this key, low cost medication are frequent (9,26). When short-acting formulations are available, patients are frequently given small supplies for fear of diversion (27)(28)(29)(30)(31).…”
Section: Palliative Infrastructure and Recent Developmentsmentioning
confidence: 99%
“…National laws and regulations governing opioids typically focus on prevention of diversion and illegal use of opioids and make production importation, and prescription of morphine and other opioids difficult or impossible (25). For this and other reasons, including supply chain logistics and a dearth of manufacturers, stock outs of this key, low cost medication are frequent (9,26). When short-acting formulations are available, patients are frequently given small supplies for fear of diversion (27)(28)(29)(30)(31).…”
Section: Palliative Infrastructure and Recent Developmentsmentioning
confidence: 99%
“…Essential treatment availability may be limited by state policy [ 1 ]. For example, some studies have found that morphine was available to only 20% of patients in low- to middle-income countries, which make up approximately 80% of the global population [ 2 ]. Disease burden may vary among different economic levels and country policies.…”
Section: Introductionmentioning
confidence: 99%
“…Pain management is a critical component of palliative care but inadequately treated pain remains a global public health problem. 1,2 Underassessment of pain has been found to be a significant cause of inadequate pain management. 3 The phrase "pain as the fifth vital sign" was initially promoted by the American Pain Society to elevate awareness of pain treatment among healthcare professionals and to make pain visiable.…”
Section: Introductionmentioning
confidence: 99%